The mechanism of miR-410-3p and miR-34c in nasopharyngeal carcinoma development and progression - Zhu, Li; Ni, Zhigang; Liang, Kuai; Tang, Yan; Zhao, Min; Chen, Chun; Yuan, Xiaolin (Cellular and Molecular Biology, 2021)
To investigate the relationship between miR-410-3p, miR-34c and nasopharyngeal carcinoma development, we detected the expression of miR-410-3p and miR-34c in nasopharyngeal carcinoma tissues and evaluate its clinical value as a molecular marker for predicting the prognosis in patients with nasopharyngeal carcinoma through clinical case study. To identify the role and mechanism of miR-410-3p and miR-34c in nasopharyngeal carcinoma development and progression. The expression of miR-410-3p and miR-34cin 300 cases of nasopharyngeal carcinoma tissues and 30 cases of paired adjacent normal breast tissues was detected by RT-qPCR. The paired t-test was used to compare the differences of miR-410-3pand miR-34c levels between the nasopharyngeal carcinoma and normal groups. The Chi-square test was used to compare the differences between miR-410-3p and miR-34c expression and clinicopathological factors. The Kaplan-Meier survival curve was used to analyze the relationship between miR-410-3p and miR-34c expression and 5-year overall survival (OS). The Cox proportional hazards regression model was used to evaluate the prognostic value. The results were validated by TCGA database. The expression of miR-410-3p was down-regulated in nasopharyngeal carcinoma tissues compared with that of paired normal tissues (P<0.001). The patients with lower miR-410-3p expression have a higher ratio of positive lymph node status (P=0.039) and a poorer 5-year disease-free survival (P=0.001) and 5-year overall survival (P = 0.002). The expression of mi R-34c was down-regulated in nasopharyngeal carcinoma tissues compared with that of paired normal tissues (P<0.001). Up-regulation of the miR-34c inhibited the viability of paired normal tissues (P<0. 01), but there was no significant change in migration of the paired normal tissues. Downregulation of mi R-34c promoted the viability and migration of paired normal tissues (P<0. 05). The expression of miR-410-3p and miR-34c levels are predictors for the OS in patients with nasopharyngeal carcinoma. The expression of miR-410-3p and miR-34c are molecular markers of early nasopharyngeal carcinoma metastasis and an independent prognostic biomarker for patients with nasopharyngeal carcinoma.